A SYSTEMATIC LITERATURE REVIEW : NONFINANCIAL DRIVERS PADA INTEGRATED REPORTING - Lissa Damayanti; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
The purpose of this study is to examine and find out what nonfinancial drivers variables affect integrated reporting. This study uses the systematic literature review (SLR) method to analyze various published journals in academic journals published in 2016 to 2022 taken from the Scopus web using predetermined search strings. Of the 20 articles used as research data downloaded from Scopus subscribed to Diponegoro University, then selected through the PRISMA method so that only 17 articles will be reviewed further. The results of the analysis found that nonfinancial drivers in the form of technology, namely social media, XBRL, the internet and green innovation reporting affect integrated reporting. Other nonfinancial drivers in the form of assurance, CSR assurance, external assurance, GCG disclosure, ISO 56002-2019 adoption, extinction accounting, integrated thinking, social, labor, environment, risk, voluntary disclosure, management commitment, regulatory enforcement, R&D investment, patents ad licenses developed by the organization, innovation, implementation of organizational strategy, investment in ERP,  hardware investment, organizational structure, ability to act remotely, technical competence of the organization’s board and fiscal council, safe working environment for the performance of professional activities, professional development policy, social inclusion policy, incentive and compensation, advertising management program for the company’s products and services, engagement programs aimed at customer loyalty and satisfaction, brand recognition and value reputation, dialogue with stakeholders, development of local infrastructure promoting the social issue of the surroundings, collaboration in business and research, relationship with suppliers, preservation of climate and environmental policies, climatic and environmental indicators, and environmental provisions also affect integrated reporting.